Sensescapes a phenomenological-multisensory approach to urban design and community branding - Esguerra, Geolette Marie Y. (Quezon City College of Architecture, University of the Philippines Diliman, 2012)
The study aims to show how a phenomenological-multisensory approach to understanding communities is desirable and advantageous. Rather than rely on the phenomenological that focuses on the Spirit of Place, the discussion is enhanced by the integration of multisensory elements--the visual, auditory, olfactory, tactile, and gustatory in an even richer description of the Spirit of Place. Using Barangay Poblacion as a case study, the author made use of the phenomenological appraoch in inquiry, making use of interviews of selected members of the community and personal narrative, and added the multisensory dimension by means of a visual analysis of contest photographs, sensewalks, and a comparative analysis by use of maps, which further strengthened the findings. In the end, it was found that Poblacion's Spirit of Place bears strong links to religion and the people. Further, the study suggests different means of using the approach, specifically in design, branding, and research.
Vita.
Thesis (Master of Architecture)--University of the Philippines, Diliman.